Growth and Development of Street Gangs - Guymon, Audrey D. (1997)
This field study of the growth and development of street gangs was conducted in the spring of 1996 at a medium security prison utilizing a semi-structured interview with 69 inmates who were known present or former gang members. Since the sample was taken from a population of convicted felons, the results reflect the environment of the participants and may not be representative of gang members as a whole. The field study determined that the majority of the participants came from two parent homes, had joined the gang between the ages of 9 and 15, lacked positive male role models, and came from both urban and nonurban areas. Peer or family pressure, survival and economics were the major factors for joining the gangs